Monitoring sodium content in packaged foods sold in the Americas and compliance with the updated regional sodium reduction targets. - Yahan Yang; Nadia Flexner; Maria Victoria Tiscornia; Leila Guarnieri; Adriana Blanco-Metzler; Hilda Núñez-Rivas; Marlene Roselló-Araya; Paola Arévalo-Rodríguez; Maria Fernanda Kroker-Lobos; Francisco Diez-Canseco; Mayra Meza-Hernández; Kiomi Yabiku-Soto; et al. (PLoS ONE)
Background Sodium reduction is a cost-effective measure to prevent noncommunicable diseases. The World Health Organization (WHO) established a target of a 30% relative reduction in mean population intake of sodium by 2025. The Pan American Health Organization (PAHO) published sodium reduction targets (SRTs) for packaged foods in 2015, expanding and updating the targets in 2021 to help Member States with its efforts in reducing population sodium intake. Objective This study examined the current sodium levels in packaged foods among five countries in the Americas and monitored cross-sectional and longitudinal compliance with the sodium targets from 2015 to 2022. Methods Food labels were systematically collected from the main supermarkets in five countries in the Americas region in 2022. Sodium levels per 100g and per kcal for collected food labels in 16 PAHO categories and 75 subcategories were analyzed and compared against the updated SRTs. Further analysis of three countries that have longitudinal data for 2015-2016, 2017-2018 and 2022 was conducted to compare sodium per 100 g against the 2015 SRTs. Results A total of 25,569 food items were analyzed. Overall, 'processed meat and poultry' had the highest sodium levels, although there were large variations within categories. 47% and 45% of products met the sodium per 100g and per kcal 2022 SRTs, respectively. Peru had the highest compliance, whereas Panama had the lowest for both targets. Among Argentina, Costa Rica and Peru, the proportion of foods meeting the 2015 PAHO lower targets were 48, 53 and 61% for 2015-2016, 2017-2018 and 2022, respectively (p < 0.001). Conclusions This study showed that around half of the examined foods met their respective SRTs and there have been small improvements in compliance over time. Further efforts are required to reach the WHO's global sodium reduction goal by 2025, such as implementation of mandatory SRTs and front-of-pack labelling regulations.